Comparison of beta-lactam/ beta-lactamase inhibitors with carbapenem for urinary bacteremia caused by ceftriaxone resistant Escherichia coli and klebsiella species - Rani, Beena; Babar, Zaheer Uddin; Dodani, Sunil Kumar; Nasim, Asma Nasim; Badlani, Sanjay Badlani (Infectious Diseases Journal of Pakistan, 2023)
Background: The debate, whether to treat ceftriaxone resistant (CROr) gram negative urinary tract infection with bacteremia (bUTI) with Beta-lactam/beta lactamase inhibitors (BL/BLI) or Carbapenem is going on. Carbapenem are expensive in our part of the world. Our aim was to see the efficacy of BL/BLI in the treatment of bUTI caused by CROr Escherichia coli (E-coli) or Klebsiella species (spp.) To compare microbiological clearance, clinical failure, new bacteremia and mortality between patients with bUTI who receive BL/BLI or Carbapenem. Material and Methods: A retrospective chart review was done at a tertiary care hospital of kidney diseases from October 2021 till June 2022. We included all adult patients with bUTI caused by CROr E-coli or Klebsiella spp, and they were excluded if bacteremia with no clear source or received antibiotics other than BL/BLI or carbapenems or received for less than 48 hours duration. Demographic characteristics, comorbidities, and clinical outcome were compared between BL/BLI and carbapenem groups. Results: A total of 41 files were reviewed. The demographics, risk factors and clinical features were comparable. We did not find statistically significant difference in microbiological clearance, clinical failure, and mortality between BL/BLI and Carbapenem groups. Conclusion: BL/BLI combinations are as efficacious as Carbapenems in CROr bUTI in terms of microbiological clearance. The clinical success and mortality were same in both groups. Keywords: bUTI, Klebsiella spp, Carbapenems, BL/BLI, Mortality, Disease severity, Microbiological clearance.